Water Purity - Bousiou, C.; Mitropoulos, S.; Moschovitis, C.; Argyri, P. (Open Schools Journal for Open Science, 2020)
The subject of this paper is the purity of water, the problems facing the whole planet in terms of it, solutions for them, as well as a little research conducted by us on our peers. Based on the theoretical framework of the work, we wanted to prove to the readers: a) The problem of water pollution has now taken on enormous proportions, and is no longer just a threat to countries far from Greece, b) there are ways to ensure drinking water for ourselves and for entire communities. Regarding the exploratory part of our work, the study involved 20 junior high school and high school students, who answered a questionnaire that examined issues such as the domestic use of water for each, their behavior towards water, etc. Then, the results were recorded and presented by means of in graphs.